Políticas de acesso a terra e desenvolvimento rural no município de Florânia (RN): entre as ações do INCRA e do Crédito Fundiário - Medeiros, Verônica Auridete Dantas (2021)
This paper analyzes two policies of access to land implemented in the city of Florânia/RN: the Agrarian Reform, which is conducted by the National State, through the National Institute of Colonization and Agrarian Reform (INCRA), as well as coordinated by the Special Secretariat of Family Agriculture and Agrarian Development (SEAD), of the Federal Government, called Market Agrarian Reform, which has the support of the World Bank (WB). These are two actions that deal with access to land and, consequently, a possible improvement in the lives of the population involved. To carry out this study, the chosen category of analysis was development, as well as recourse to the concepts of rural development and public policies. Thus, this research has as a general objective: to analyze the policies of access to land (the Constitutional Agrarian Reform and the Market Agrarian Reform), emphasizing the viability of the development of the focus areas of these policies and of the rural population served by them in the city of Florânia (RN), in a period that extends from 1998 to 2019 (the period in which all settlements were built in that city). Based on bibliographic, documental and field research, this study was developed and systematized, besides the introduction, in three chapters. For the first chapter, an approach is presented about the concepts of development and rural development, as well as public policies created for the Brazilian countryside. At this stage, these concepts are debated, since these policies can be considered important instruments used in the search for development. In the second chapter, the objective is to analyze the dynamics of the functioning of the two existing policies of access to land in Brazil and Rio Grande do Norte, in the context of rural settlements. In the third chapter, we seek to know the performance and spatialization of the Constitutional Agrarian Reform and the Market Agrarian Reform in the city of Florânia (RN). In it, a comparison between these two policies was also carried out, through which it was observed that the action of the Constitutional Agrarian Reform stands out and excels in the researched city, regarding the viability of the development of the place and its population, when compared to the execution of the MRA.